2021
DOI: 10.1021/acs.nanolett.1c02240
|View full text |Cite
|
Sign up to set email alerts
|

Operando Investigation of Locally Enhanced Electric Field Treatment (LEEFT) Harnessing Lightning-Rod Effect for Rapid Bacteria Inactivation

Abstract: The growth of undesired bacteria causes numerous problems. Here, we show that locally enhanced electric field treatment (LEEFT) can cause rapid bacteria inactivation by electroporation without any side reactions. The bacteria inactivation is studied in situ at the single-cell level on a lab-on-a-chip that has nanowedge-decorated electrodes. Rapid bacteria inactivation occurs specifically at nanowedge tips where the electric field is enhanced due to the lightning-rod effect. The mechanism study shows that the b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…The typical operation processes of NWs-FES at 2.5 and 3.5 V revealed that the balance of ARB or ARG adsorption and desorption resulted in stable operation after operation for 10 min, and the stable operation performance and limited release of Co species within 50 h of continuous operation suggested excellent stability of the Co 3 O 4 -NWs electrodes (see more details in Figure S2). The ARB and i-ARG removal by the NWs-FES increased significantly with the increase of applied voltage or decrease of flux (Figures and S3), which was consistent with the findings from previous work. , Notably, the i-ARGs were much more recalcitrant than the ARB to the FES treatment due to the protective roles of cellular components, but the NWs-FES exhibited much higher efficiencies in the removal of ARB and ARG than the Film-FES. For instance, as compared with the above 6.7 log ARB removal (undetectable live ARB in effluent) and ∼0.5 log ARG removal by Film-FES at 3.5 V and 1000 L/m 2 /h, the NWs-FES achieved above 6.7 log ARB removal and ∼1.5 log ARG removal at only 2.75 V. The energy consumption by NWs-FES (20–60 W h/m 3 /log) was ∼6–9 times lower than that by Film-FES (200–350 W h/m 3 /log) (Figure S4).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The typical operation processes of NWs-FES at 2.5 and 3.5 V revealed that the balance of ARB or ARG adsorption and desorption resulted in stable operation after operation for 10 min, and the stable operation performance and limited release of Co species within 50 h of continuous operation suggested excellent stability of the Co 3 O 4 -NWs electrodes (see more details in Figure S2). The ARB and i-ARG removal by the NWs-FES increased significantly with the increase of applied voltage or decrease of flux (Figures and S3), which was consistent with the findings from previous work. , Notably, the i-ARGs were much more recalcitrant than the ARB to the FES treatment due to the protective roles of cellular components, but the NWs-FES exhibited much higher efficiencies in the removal of ARB and ARG than the Film-FES. For instance, as compared with the above 6.7 log ARB removal (undetectable live ARB in effluent) and ∼0.5 log ARG removal by Film-FES at 3.5 V and 1000 L/m 2 /h, the NWs-FES achieved above 6.7 log ARB removal and ∼1.5 log ARG removal at only 2.75 V. The energy consumption by NWs-FES (20–60 W h/m 3 /log) was ∼6–9 times lower than that by Film-FES (200–350 W h/m 3 /log) (Figure S4).…”
Section: Resultssupporting
confidence: 91%
“…The ARB and i-ARG removal by the NWs-FES increased significantly with the increase of applied voltage or decrease of flux (Figures 2 and S3), which was consistent with the findings from previous work. 26,27 Notably, the i-ARGs were much more recalcitrant than the ARB to the FES treatment due to the protective roles of cellular components, but the NWs-FES exhibited much higher efficiencies in the removal of ARB and ARG than the Film-FES. For instance, as compared with the above 6.7 log ARB removal (undetectable live ARB in effluent) and ∼0.5 log ARG removal by Film-FES at 3.5 V and 1000 L/m 2 /h, the NWs-FES achieved above 6.7 log ARB removal and ∼1.5 log ARG removal at only 2.75 V. The energy consumption by NWs-FES (20−60 W h/m 3 /log) was ∼6−9 times lower than that by Film-FES (200−350 W h/m 3 /log) (Figure S4).…”
Section: Characterization Of Comentioning
confidence: 99%
“…The free chlorine concentration was determined through the N , N -diethyl-1,4-phenylenediamine sulfate method using an assay kit (Hanna, HI97710) and measured through a spectrophotometer at a wavelength of 515 nm. DMSO (5%) was used to quench all the electrogenerated oxidative species, causing the disinfection system to rely solely on electroporation when DMSO was added. Additionally, nitrogen gas was bubbled to selectively inhibit the generation of oxygen gas-mediated reactive species, such as • O 2 – and H 2 O 2 , without affecting the active chlorine generation.…”
Section: Methodsmentioning
confidence: 99%
“…For the in situ double staining method, 5 mM of SYTOX Green was first added to the bacteria-containing feed solution before performing the disinfection process. , After disinfection, 20 μL of effluent was added onto a poly- l -lysine coated chip. A layer of cells was immobilized on the chip surface after settling for 30 min, and the cells were then observed using fluorescence microscopy (Zeiss, Axio Imager 2).…”
Section: Methodsmentioning
confidence: 99%
“…A triboelectric nanogenerator (TENG), a triboelectrification- and charge-induction-based energy harvester, can convert the flow of water to electricity under low-intensity stimuli, which is promising for self-powered POU water disinfection . Owing to high output voltages (>200 V), TENGs are competent in driving a nanowire-assisted electroporation disinfection process, which effectively damages bacterial membranes through a highly localized electric field at the wire tip. A ball-in-ball TENG harnessing wave energy was developed to drive an electroporation system using ZnO-nanowire-modified electrodes for self-powered disinfection . However, electroporation occurs only when bacteria approach the nanowire tip with enhanced localized electric fields .…”
mentioning
confidence: 99%